(3LQjeI GdGJUGd ZjQ GdeTQhY HOhdI CLfHjI aj GdbGfhf GdLfGFj Gdjefj (B: s (3OQGSI ebGQfI (B/ s - (3CMeO SGde eMeO GdLfjOjs; (3YeQ eMeO SGde (B: s ((3GdbGgQI (B: s (3CMeO SGde eMeO GdLfjOj (B: s, 2013)
(3JYO LQjeI GdGJUGd ZjQ GdeTQhY HOhdI CLfHjIq GdJLSqS ef CNWQ GdLQGFe GdhGbYI Ydi Cef GdOhdI ef LgI GdNGQL agj JTcd NWQB Ydi cjGf GdOhdI h SdGeJgG (B: (3h hbhYgG jJQJH Yfg VQQ HdjZ jUjH GdOhdI aj cjGfgG HTcd YGe (B: (3Hd Cf eOGg bO jJSY djJfGhd GdCeI HCSQgG (B: (3dgPG JMQU GdOhd cGaI Ydi HbGA WGFaI cHjQI ef GdeYdheGJ h GdHjGfGJ aj Wj GdcJeGf Yf cd CLfHj YfgG (B: (3Hd ef cd Yf de jfW Edjg CeQ MaXgG h GdGWdGY YdjgG HMce hXjaJg h egfJgs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFis
(3UOQ GjVG cbQU eOeLs
Keywords: (3EaTGA CSQGQ GdOaGY GdhWfjs; (3GdGJUGd ZjQ GdeTQhY HOhdI CLfHjIs; (3GdJNGHQs